Academie St-Joost Breda. - Gremmen, Hans; Rombouts, Heidi; Gofers, Monique; Willems, Roger; Academie St-Joost, Breda; Staal, Gert; Nijenhuis, Peter (Breda : Academie St-Joost, 2000)
Polat, Ahmet ; Ozoen, Isil ; De Boorder, Jeroen ; Nash, Susan ; Koster, Charlotte ; Oomens, Marieke ; Clement, Tijl ; Keerseweer, Anne-Marie ; Rosema, Stephen ; et al.
Eindexamententoonstelling van de Academie, vermoedelijk juni 2000 in Academie St-Joost, Breda
kunstcatalogus